1995
DOI: 10.1063/1.470166
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical calculations of tunneling splitting in malonaldehyde

Abstract: We have devised a semiclassical procedure based on the Makri–Miller [J. Chem. Phys. 91, 4026 (1989)] model for calculating the eigenvalue splitting in many-atom systems and have used it to calculate the ground-state splitting in several isotopomers of malonaldehyde. A potential-energy surface that includes all twenty-one vibrational degrees of freedom was constructed based on the available theoretical and experimental information. The results for calculations in which all atoms are allowed full three-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 32 publications
8
91
0
Order By: Relevance
“…Since then the determination of the ground state tunneling splitting of MA has been the focus of several studies ranging from reduced dimensionality quantum calculations 7,8 to elaborate full-dimensional semiclassical treatments. [9][10][11][12][13][14][15][16][17] Most of these studies employed MA as a test case for method development measuring the accuracy of the calculation by comparing the computed value of the ground state splitting with the experimental one.…”
Section: Introductionmentioning
confidence: 99%
“…Since then the determination of the ground state tunneling splitting of MA has been the focus of several studies ranging from reduced dimensionality quantum calculations 7,8 to elaborate full-dimensional semiclassical treatments. [9][10][11][12][13][14][15][16][17] Most of these studies employed MA as a test case for method development measuring the accuracy of the calculation by comparing the computed value of the ground state splitting with the experimental one.…”
Section: Introductionmentioning
confidence: 99%
“…[15,19]. Indeterminate e Sewell et al [62]. Vibrations from the utilized PES correlate poorly with the observed midrange vibrations.…”
Section: Coherent Tunneling Splitting Phenomena In Malonaldehyde 11mentioning
confidence: 91%
“…In column 4 the D V /D 0 ratios are listed next to theoretical ratios [61][62][63][64] discussed below. Of the nine experimental values only the four lower frequency skeletal displacements -two in-plane and two out-ofplane -appear to significantly impact the tunneling process.…”
Section: Coherent Tunneling Splitting Phenomena In Malonaldehydementioning
confidence: 99%
See 1 more Smart Citation
“…Several examples of such approaches exist; for example, a model used by Miller and co-workers 10,11 (which is patterned after Tully and Preston's surface-hopping models for treating electronically nonadiabatic processes 12 ) is a fairly primitive way of describing tunneling processes with only real-valued trajectories, but it has found some utility. [13][14][15][16][17][18][19] Within the semiclassical (SC) initial value representation (IVR), it has also been shown that purely real-valued classical trajectories can describe tunneling processes to a very useful extent. [20][21][22] (The very reason the IVR was first introduced, 23 in fact, was to be able to describe classically forbidden vibrationally inelastic scattering with realvalued trajectories.…”
Section: Introductionmentioning
confidence: 99%